Пьер-Огюст Ренуар - Роньшин Валерий Михайлович (Исторический роман, 2006)
Экземпляры: ф. 2 (20101126) / Инвентарный номер: 96676 / Цена: 140 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Р 71 / ББК: 84(2Рос=Рус)6